"What's next?" Individual differences in expected repercussions of the COVID-19 pandemic. (May 2021) - Ceccato, Irene; Palumbo, Rocco; Di Crosta, Adolfo; Marchetti, Daniela; La Malva, Pasquale; Maiella, Roberta; Marin, Anna; Mammarella, Nicola; Verrocchio, Maria Cristina; Di Domenico, Alberto
Abstract: The effects of the COVID-19 pandemic on the future are hardly predictable, and people differ in terms of expected repercussions on their future. This study investigated individual differences in the pandemic's expected repercussions, with particular attention to a Balanced Time Perspective (BTP). BTP reflects an individual profile with optimal temporal orientations, it is positively associated with mental health, and it has proven to promote successful coping with unexpected crises. We analyzed data from 3991 adults from 18 to 85 years old participating in an online survey conducted during the Italian lockdown. Participants provided information on BTP, affective states, financial resources, and expectations for the future. Multi-group path analysis was used to test the hypothesized model and to explore gender differences. Results showed that people with a more BTP had fewer negative beliefs about COVID-19's consequences on their future life. BTP affected expected repercussions also indirectly, via affects and beliefs. Finally, gender emerged as a significant moderator of some of the relationships highlighted. The present study contributes to the understanding of the psychological reactions to the current health emergency by confirming its impact on several life domains besides health, not only in the present but also in the anticipated future. Highlights: Individual differences in the expected repercussions of the COVID-19 pandemic were found. Time perspective is related to negative affect and beliefs about COVID-19's consequences. Balanced time perspective predicted expected repercussions through affects and beliefs. Gender differences on backlashes due to COVID-19 exist.